Methotrexate - pharmacological properties and its application in pharmacotherapy - Dawid Frączkowski; Łukasz Szeleszczuk (Polish Pharmaceutical Society, 2020)
Methotrexate (MTX), a structural analogue of folic acid, is one of the most extensively used and effective drugs for treating many kinds of tumour and autoimmune diseases. In this review, an overview of the present state of knowledge with regards to methotrexate applications as immunosuppressive drug and chemotherapeutic agent has been presented. Despite the introduction of numerous biologic agents for the treatment of rheumatoid arthritis (RA) and other forms of inflammatory arthritis, low-dose methotrexate therapy remains the gold standard in rheumatoid arthritis therapy. Methotrexate is the first-line drug for the treatment of rheumatoid arthritis, psoriatic arthritis and other forms of inflammatory arthritis. In this review, the pharmacology and metabolic and cellular mechanisms by which methotrexate suppresses inflammation have been discussed. Methotrexate, as a drug, has a pleiotropic mechanism of action. It affects the metabolism of cancer cells by inhibiting the enzyme responsible for the metabolism of folic acid, which leads to a deficiency of folic acid in the cells and their death. Understanding the mechanism of action of methotrexate could be instructive in the appropriate use of the drug and in the design of new regimens for the treatment. The mechanisms discussed in this review are general and, although these mechanisms are best documented in rheumatoid arthritis, they could apply to other forms of inflammatory arthritis. The article also provides information on the history of methotrexate, its Anatomical Therapeutic Chemical Classification System, routes of administration, dosage, side effects, and drug interactions. Methotrexate has been used over 60 years to treat variety of autoimmune disorders with the same or greater efficacy than most other synthetic DMARDs (disease-modifying antirheumatic drugs), e.g., AZT (azidothymidine), and is also used alone or in combination with other anticancer agents in different types of cancer treatments and still remains of great interest to researchers all over the world. Methotrexate is still widely used in the treatment of various diseases and has not been allowed to become a thing of the past. The low cost combined with good long-term efficacy and safety profile justify the use of methotrexate as a first-line disease-modifying or steroid sparing drug in many of these diseases.